Analisis Implementasi Pendidikan Karakter dalam Pembelajaran Daring Di SDN Menteng Dalam 07 - Dewi Octavia A; Qori Septiani; Rachma Alya Maulidhia; Desi Rahmawati (Risenologi, 2021)
The Covid-19 pandemic condition makes all activities carried out online, one of which is the teaching and learning process. This is a challenge for the world of education, especially in an effort to improve the nation's character education. Therefore, this study aims to analyze the implementation of character education through online learning at SDN Menteng Dalam 07. This research is descriptive qualitative with literature study documentation and interviews, in which researchers try to provide solutions to the implementation of character education in the online teaching and learning process. The results of this study indicate that: contributions between teachers/schools, parents, and the environment are important in improving the character of students, and the concern of teachers and parents is the main key to the successful implementation of character education in online learning.